Sosialisasi Kewirausahaan Melalui Pemanfaatan Hasil Produksi Pisang dan Ayam Potong untuk Meningkatkan Kesejahteraan Masyarakat - Triyanto Triyanto; Irma Juraida; Rahma Husna Yana (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2019)
A country's economy is determined by government revenue, and government revenue is also closely related to regional income. Meanwhile, regional income is also related to community income. Many opportunities can improve the economy. Khairil Anwar's research revealed that many of the items sold in the city of Meulaboh and the surrounding area came from other regions both inside and outside the Aceh region. Of course, if this can be done by the people of West Aceh, the community's economy will improve. To improve community welfare, it is important to gain insight into the community. The method of implementation is to gather parishioners and then give them an overview of the results of research on goods used and consumed by the community. Then together, calculate the potential that can be done. As a result, the community has realized many ways to increase family income while increasing welfare by only planting bananas and chicken pieces.